The Interruption of inferior vena cava in treatment of pulmonary thromboembolism.: Indications and results - Delgado, Bolívar; Soto, José A; Gateño, Nisso (Cirugía del Uruguay, 1979)
Interruption of the inferior vena cava in treatment of pulmonary thromboembolism, is still subject to ccntroversy. On the basis of a case material consisting in 23 operations, the authors review the subject, with the accent on indications and results. In. this series the most frequent indications were failure or éontraindication of anticoagulant treatment, rep